AB0593 Predictors of fatigue and severe fatigue in a large multicenter international cohort of patients with systemic lupus erythematosus: the fatilup study. (12th June 2018) - Arnaud, L.; Gavand, P.-E.; Amoura, Z.; Blaison, G.; Voll, R.; Schwartzing, A.; Magy Bertrand, N.; Maurier, F.; Pennaforte, J.-L.; Poindron, V.; Kieffer, P.; Bonnote, B.; et al.
Abstract : Background: Fatigue is an important issue in systemic lupus and has a major impact on quality of life of the patients. Data are controversial about the factors associated with this complex symptom. 1 Objectives: To identify the factors associated with fatigue and severe fatigue in patients with systemic lupus erythematosus (SLE) in a large cohort using a multivariate model to precise the importance of each parameter in this multidimensional symptom. Methods: We used the LBBR data base, a German French data base of SLE patients. All patients fulfilled the 1997 ACR criteria for SLE. The Fatigue Scale for Motor and Cognitive Functions (FSMC) was used to assess fatigue and severe fatigue. The depression and anxiety were measured with Hospital Anxiety and Depression Scale (HADS). Tests were performed at sampling. Results: A total of 570 patients were included (89.1% female). The median age was 42 years (QR25–75: 34–52). The median value of the SELENA-SLEDAI was 2 (QR25–75: 0–4) and 136 patients had a SELENA-SLEDAI score >6. Fatigue was reported by 386 patients (67.7%) including severe fatigue by 209 (36.7%). In univariate analysis among the individual components of the SLEDAI arthritis (p=0.003) and oral ulcers (p=0.002) were associated with severe fatigue. In multivariate analysis fatigue was strongly associated with anxiety (OR: 4.49 [95%CI: 2.60–7.77], p<0.0001) and depression (OR: 4.72 [95%CI: 1.39–16.05, p=0.01]. It was also associated with age at sampling (OR: 1.01 [95%CI: 1.00–1.03, p=0.03] per 1 year increase), SLEDAI (OR: 1.05 [95%CI: 1.00–1.12, p=0.043] per 1 SLEDAI point increase) and glucocorticoids treatment (OR: 1.54 [95%CI: 1.00–2.38, p=0.04]). It was not associated with physical activity. Severe fatigue was strongly associated with depression (OR:6.87 [95%CI: 3.12–15.11], p<0.0001) and anxiety (OR: 3.80 [95%CI: 2.46–5.87], p<0.0001) but not with SLEDAI or physical activity. Conclusions: Fatigue is a common symptom in SLE patients and is strongly associated with anxiety and depression. While remission remains an important therapeutic target, these manifestations should also be taken care of with psychological counselling and pharmacological intervention, when needed. Reference: [1] Cleanthous S, Tyagi M, Isenberg DA, Newman SP. What do we know about self-reported fatigue in systemic lupus erythematosus?Lupus. 2012Apr;21(5):465–76 Disclosure of Interest: None declared